Poetics of the artistic image (Eurasian Journal of Philology Science and Education, 2021)
The article deals with the main objects of study of literary criticism - the objective-cognitive and subjective-creative aspects of the artistic image. Since the artistic image is the result of the artist's knowledge of the truth and creative thinking, it has been proven that this is a literary category with aesthetic power, metaphorical meaning and multifaceted properties. On the basis of comparisons of world and domestic literature, define on the history of the formation and development of an artistic image, created by the author in various artistic approaches are formulated. The main purpose of the article is to show through contextual analysis that the mastery of imagination and artistic thinking of the writer is reflected in the ability to create an artistic image. The main results and conclusions of the study boil down to the fact that an image is a whole system with its own laws and individual characteristics. Since the image is a reflection of thoughts and mood, it has properties of a material and emotional nature. There are many ways to define and create an artistic image. To classify an artistic image, it is necessary to highlight several key features, such as genre, thematic, typical, archaic, semantic, structural and stylistic. The article also offers new judgments about the versatility of the artistic image, in its wide semantic range, generalized and individual characteristics. With the help of the above examples, it is confirmed that any phenomena and abstract concepts in objective reality are reflected in the form of an image presented in aesthetic consciousness. The main ideas presented in the study are important for a deeper understanding of the nature of the artistic image, the ability to classify the types of images according to their individuality.Keywords: Artistic image, imagery, aesthetic category, objective-cognitive aspects, subjective-creative approach